2013
DOI: 10.2106/jbjs.k.01476
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Findings in Symptomatic Versus Asymptomatic Subjects Following Metal-on-Metal Hip Resurfacing Arthroplasty

Abstract: An adverse synovial reaction was detected on MRI in both symptomatic and asymptomatic subjects. We found a larger volume of synovitis in symptomatic patients; this increase reached significance only in the group with an adverse local tissue reaction. Synovial volume on MRI may be a valuable marker in the longitudinal assessment of asymptomatic patients with a metal-on-metal hip resurfacing and in identifying patients with adverse local tissue reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
49
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 2 publications
5
49
0
Order By: Relevance
“…Good repeatability was demonstrated between examiners for the assessment of synovial volume using MRI. Although synovitis was noted in a similar proportion of all groups, osteolysis was rare [28]. Further longitudinal assessment of these cohorts could potentially disclose the clinical relevance of smaller synovial volumes in these patients in a variety of bearing surfaces.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 87%
See 3 more Smart Citations
“…Good repeatability was demonstrated between examiners for the assessment of synovial volume using MRI. Although synovitis was noted in a similar proportion of all groups, osteolysis was rare [28]. Further longitudinal assessment of these cohorts could potentially disclose the clinical relevance of smaller synovial volumes in these patients in a variety of bearing surfaces.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 87%
“…Recent studies pertaining to MRI have focused on potential predictive factors of soft tissue destruction seen intraoperatively at the time of revision surgery [27][28][29]. In predictive models, the maximum synovial thickness and the presence of solid synovial deposits on MRI have greater sensitivity and specificity in detecting ALVAL scores and quantifying intraoperative tissue damage than isolated serum ion levels (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This observation implies that earlier recognition of the clinical entity and diagnosis prompting earlier intervention may play a role in reducing the complications associated with wear and corrosion. Current research is focusing on routine use of three-dimensional imaging to diagnose corrosion and MoM wear problems before there is extensive soft tissue damage [16,35]. Many of the studies we identified also mentioned the use of metal level testing.…”
Section: Discussionmentioning
confidence: 99%